82 Effect of Washington and Colorado's Cannabis legalization on completed suicides. (5th May 2020) - Doucette, Mitchell L; Borrup, Kevin; Whitehill, Jennifer; Crifasi, Cassandra K; Lapidus, Garry
Abstract : Statement of Purpose: In the U.S., death by suicide is a leading cause of death and was the 2nd leading cause of death for ages 15 to 24 in 2017. Though incomplete, much of the scientific literature has found associations between cannabis use and death by suicide. As 8 states and the District of Columbia now permit recreational sale of cannabis, we sought to evaluate whether cannabis legalization has impacted suicide rates in Washington State and Colorado, the earliest states to legalize. Methods: We used a quasi-experimental research design with annual, state-level deaths by suicide data to evaluate the legalization of cannabis in Washington State and Colorado. Outcome data was from the National Center for Health Statistics-Restricted Vital Statistics. We used synthetic control models to construct policy counterfactuals, controlling for time-invariant and time-variant factors as our primary method of estimating the effect of legalization, stratified by age, gender, and mechanism. Results: Preliminary results suggest that 3-years post-implementation of recreational sale of cannabis, Washington state saw 2.8% increase in suicides, while Colorado saw a 6.5% reduction in suicides. However, both states saw increases in deaths by suicide among youth age 15 to 24 years (WA=20.2%; CO=14.9%). Additional results will discuss suicide completion stratified by mechanism and gender. Conclusion: Preliminary results suggest that the overall effect of recreational cannabis on deaths by suicide is heterogenous. However, as deaths by suicides among 15 to 24-year olds increased post-implementation in both states, states with legalized cannabis, and states considering similar legislation, may need to consider the mental health implications of cannabis legalization for younger users